Comparison of the indirect immunofluorescence assay and a commercial ELISA to detect KSHV antibodies - Valentin Leducq; Léa Ben Said; Sophie Sayon; Vincent Calvez; Anne-Geneviève Marcelin; Aude Jary (Microbiology Spectrum)
ABSTRACT Kaposi’s sarcoma-associated herpesvirus (KSHV) is an oncogenic virus involved in several diseases. The gold standard for KSHV sero diagnosis remains the indirect immunofluorescence assay (IFA), which is time-consuming and operator-dependent. We compared this method with an enzyme-linked immunosorbent assay (ELISA) targeting solubilized KSHV whole-genome extract among positive (n = 49, including 76% of HIV-infected patients) and negative (n = 14) control groups. We also included 14 sera with equivocal IFA results. ELISA showed better performance in detecting KSHV antibodies (McNemar’s test, P = 0.0455). The sensitivity and specificity of both methods were 79% (64–89) and 100% (66–100) for the IFA, respectively, and 94% (83–99) and 100% (66–100) for ELISA, respectively. All IFA equivocal results were either negative or positive with ELISA. ELISA is more reliable and could be a good alternative for determining KSHV serological status, particularly in the context of immunocompromised patients and equivocal serology with the IFA.IMPORTANCEKaposi’s sarcoma-associated herpesvirus (KSHV) sero status remains challenging because no perfect reference is available for the detection of KSHV antibodies. The current gold-standard method, the indirect immunofluorescence assay (IFA), has a very good specificity of close to 100%, but a lower sensitivity of around 80–85%, which decreases to 64–67% in immunocompromised patients. Additionally, this method is time-consuming and operator-dependent compared with new serological assays such as the enzyme-linked immunosorbent assay (ELISA). Thus, further research is still needed to improve KSHV sero diagnosis. Here, we compare the KSHV IgG ELISA kit assay (Advanced Biotechnologies Inc) with the gold-standard IFA, targeting the LANA-1 protein from latent BC-3 cell lines.